2018
DOI: 10.1186/s12967-018-1735-9
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota dysbiosis in male patients with chronic traumatic complete spinal cord injury

Abstract: BackgroundNeurogenic bowel dysfunction (NBD) is a major physical and psychological problem in patients with spinal cord injury (SCI), and gut dysbiosis is commonly occurs in SCI. Here, we document neurogenic bowel management of male patients with chronic traumatic complete SCI in our centre and perform comparative analysis of the gut microbiota between our patients and healthy males.MethodsA total of 43 male patients with chronic traumatic complete SCI (20 with quadriplegia and 23 with paraplegia) and 23 healt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
4
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 58 publications
5
116
4
4
Order By: Relevance
“…Accumulating evidence suggests that gut microbial dysbiosis may be involved in SCI pathogenesis and clinical manifestations [22,23,25]. In the present study, we found that FMT not only reshaped microbiota in SCI mice, but also improved neurological functions of SCI mice.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Accumulating evidence suggests that gut microbial dysbiosis may be involved in SCI pathogenesis and clinical manifestations [22,23,25]. In the present study, we found that FMT not only reshaped microbiota in SCI mice, but also improved neurological functions of SCI mice.…”
Section: Discussionsupporting
confidence: 68%
“…Anaeroplasmatales and open-field locomotor has been observed in SCI mice, indicating that the proportion of these bacteria might predict the size of functional recovery [22]. Recent investigations demonstrated that induced gut dysbosis exacerbates lesion pathology and impairs functional recovery after SCI; whereas remodeling gut microbes is beneficial to locomotor recovery following injury [25,23].…”
Section: Strong Correlation Between the Relative Abundance Of Clostrimentioning
confidence: 99%
See 1 more Smart Citation
“…The human gastrointestinal tract is colonized by 100 trillion bacteria, the composition and function of which is susceptible to a plethora of environmental (diet, medication use, physical activity, etc) and host genetic factors. In the case of SCI, the loss of central nervous system control over the gastrointestinal tract, neurological bowel dysfunction and altered colonic transit time are implicated in disruption of the gut microbiota composition (i.e., gut dysbiosis (GD)) [21][22][23][24] . GD developing shortly after SCI is accompanied by inflammation of the intestine [22,23], increased intestinal permeability (leaky gut), and bacterial translocation from the gut into distal organs [23].…”
Section: Introductionmentioning
confidence: 99%
“…and host genetic factors. In the case of SCI, the loss of central nervous system control over the gastrointestinal tract, neurological bowel dysfunction and altered colonic transit time, are implicated in disruption of gut microbiota composition (i.e., gut dysbiosis [GD]) (21)(22)(23)(24) . GD developed shortly after SCI is accompanied by inflammation of the intestine (22,23), increased intestinal permeability (leaky gut), and bacterial translocation from the gut into distal organs (23).…”
Section: Introductionmentioning
confidence: 99%